Promoting Teachers’ Learning and Knowledge Building in a Socio-Technical System - Tammets, Kairit; Pata, Kai; Laanpere, Mart (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2013)
The study proposes a way in which the learning and knowledge building (LKB) framework, which is consistent with the knowledge conversion phases proposed by Nonaka and Takeuchi, supports teachers’ informal and self-directed workplace learning. An LKB framework in a socio-technical system was developed to support professional development in an extended professional community. The LKB framework was implemented and formatively evaluated in the in-service course that prepares teachers for accreditation in an e-portfolio community. The extended community consisted of 16 participants, in-service teachers and domain experts. The evaluation considered (a) how the LKB practices of the framework became actualized among the community members and (b) what supported these LKB practices. Data were collected from log-files of the portfolio system. Correlation analysis and Bayesian dependency modelling revealed the way in which the bottom-up peer scaffolding from community members influences teachers’ LKB practices. As a result, the study proposes that a socio-technical system might promote LKB in a professional community.